Spillovers and connectedness between green bond and stock markets in bearish and bullish market scenarios - Mensi, Walid; Shafiullah, Muhammad; Vo, Xuan Vinh; Kang, Sang Hoon (Finance research letters, 2022)
•This study examines the quantile connectedness between eight green bonds and the S&P 500 index.•Green bonds and the S&P 500 index exhibit stronger connectedness during crises.•Green bonds are relatively less volatile during extraordinary events.•The quantile spillover largely originates from their energy and resource. This study examines the quantile connectedness between eight green bonds and the S&P 500 index using the methodology of Ando et al. (2022). We show that green bonds and the S&P 500 index exhibit stronger connectedness during crises (GFC, COVID-19, etc.). Furthermore, green bonds are relatively less volatile during extraordinary events. The distribution tails dictate connectedness (short-term) in the wake of extreme events. The quantile spillover in the green financial markets largely originates from their energy and resource (water conservation) counterparts. These observations underscore the prevalence of upside, downside, and tail risks from green stock markets, particularly following crisis events.